Using case study in education research - Hamilton, Lorna (Lorna C.).; Corbett-Whittier, Connie (Los Angeles, Calif. : SAGE, 2013)
Case study research is often thought of as a rather a theoretical research approach. In this book the authors present a picture of case study which focuses on ideas as a foundation for investigation, and which highlights the place of this case study as a key component of educational research. This book provides an accessible introduction to using case studies. It makes sense of literature in this area, and shows how to generate collaborations and communicate findings. The authors bring together the practical and the theoretical, enabling readers to build expertise on the principles and practice of case study research, as well as engaging with possible theoretical frameworks. With the help of this book, M-Level students, teacher educators and practitioner researchers will gain the confidence and skills needed to design and conduct a high quality case study. Research Methods in Education series: Each book in this series maps the territory of a key research approach or topic in order to help readers progress from beginner to advanced researcher. Each book aims to provide a definitive, market-leading overview and to present a blend of theory and practice with a critical edge. All titles in the series are written for Master's-level students anywhere and are intended to be useful to the many diverse constituencies interested in research on education and related areas. Other books in the series: - Qualitative Research in Education, Atkins and Wallace - Action Research in Education, McAteer - Ethnography in Education, Mills and Morton.
Machine generated contents note: Section 1 The case study approach in education research -- 1.Defining case study in education research -- 2.Ideas as the foundation for case study -- Section 2 Choosing the case study route -- 3.Key purposes -- 4.Key decisions -- 5.Ethics in research -- Section 3 Doing a case study -- 6.Carrying out your case study -- 7.A practitioner perspective -- 8.Approaches to data analysis -- 9.Using technology to manage and analyse your data -- Section 4 Disseminating and defending case study approaches -- 10.Finding your voice -- 11.Sharing case study: quality and communication -- Section 5 Community and networking -- 12.Virtual environments and collaborations -- 13.Community building.
Includes bibliographical references and index.
Keywords: Education -- Research -- Methodology; Case method